Pertanggungjawaban Komando dalam Pelanggaran Hak Asasi Manusia di Indonesia - Pravidjayanto, Mochammad Rafi; Alfatoni, Muhammad Aqil; Fajrin, Muslihah Yunita (Department of Comparative Mazhab Comparative, Fakulty of Shariah and Law, 2024)
Abstract: The ineffectiveness of legal norms in Article 42 paragraphs (1) and (2) of Law Number 26 of 2000, which contains the material of command accountability, has implications for the impunity of gross human rights violators committed by law enforcement officials. This paper aims to find out the principles, problems, and ideal concepts in command accountability, which will then be internationalised in the National Code of Law (KUHP) with the hope that in the future the a quo article can be effective in ensnaring perpetrators of gross human rights violations, through juridical-normative methods with a conceptual approach, and a statute approach. The results of this article are, first, the existence of inequality in subjective elements in Articles 598-599 of the National Criminal Code, which relates to gross human rights, and Article 42 of Law Number 26 of 2000. This has the potential to ensnare the legal subject of citizens who incidentally are not obligors, so that it is more effective to include the element of command accountability in the explanation of the word